PENGARUH KETERLIBATAN PEMAKAI, KEMAMPUAN PEMAKAI, PELATIHAN DAN PENDIDIKAN PEMAKAI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Kharisma, Ida Ayu Mira; Juliarsa, Gede (E-Jurnal Akuntansi, 2017)
The purpose of this study was to determine the effect of the involvement of users, the ability of users, training and user education on the performance of accounting information systems at Inna Grand Bali Beach. This study took a sample of the entire staff accounting department Inna Grand Bali Beach based non-probability sampling method with saturated sampling techniques and sample of 46 staff. Data collection was conducted by survey method. The data in this study using multiple linear regression analysis. The analysis showed that the involvement of users, the ability of users positive and significant impact on the performance of accounting information systems at Inna Grand Bali Beach while training and user education has no significant effect on the performance of accounting information systems at Inna Grand Bali Beach.
Keywords: the involvement of users, the ability of users, training and user education, accounting information system performance